2006
DOI: 10.1159/000095902
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Soluble TNF-α Receptors and Cellular Adhesion Molecules in Patients Undergoing Bioincompatible Hemodialysis

Abstract: Background: The study aimed to differentiate the effects of hemodialysis (HD) and chronic renal failure (CRF) on the levels of circulating tumor necrosis factor-α (TNF-α) and TNF-α receptors p55 and p75, soluble vascular cell adhesion molecule-1 (sVCAM-1), intercellular adhesion molecule-1 (sICAM-1), soluble endothelial-leukocyte adhesion molecule-1 (sE-selectin) and sP-selectin in 18 patients on regular HD treatment with cuprophane membrane in relation to 15 non-dialyzed CRF patients and 15 healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 41 publications
2
12
0
2
Order By: Relevance
“…The same cell model demonstrated that H 2 O 2 , similarly to increased oxidative stress in HD patients, induced a decrease in lymphocyte TIMPs in parallel with increased MMP/TIMP activity, similarly to the patterns observed in our patients during HD sessions. The striking similarity of these relations might imply that the changes in MMPs and TIMPs in the serum of HD patients could originate in lymphocytes and endothelial cells subjected to enhanced generation of reactive oxygen species during HD, similarly to findings from other studies [15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 75%
“…The same cell model demonstrated that H 2 O 2 , similarly to increased oxidative stress in HD patients, induced a decrease in lymphocyte TIMPs in parallel with increased MMP/TIMP activity, similarly to the patterns observed in our patients during HD sessions. The striking similarity of these relations might imply that the changes in MMPs and TIMPs in the serum of HD patients could originate in lymphocytes and endothelial cells subjected to enhanced generation of reactive oxygen species during HD, similarly to findings from other studies [15][16][17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 75%
“…Some of these proteins induce IR, while others play a role in glucose and lipid metabolism; some are inflammatory cytokines, while others are involved in vascular hemostasis [32] . Uremia is also associated with elevation of some of the recently identified adipokines [33] . High leptin levels in CRF correlate with insulin levels [34] .…”
Section: Increased Mediators Secreted By Adipose Tissuementioning
confidence: 99%
“…Other reports found increased expression of graft kidneys when compared with chronic renal failure before transplantation [10][11][12]. Schwarz et al found increased expression of adhesive antigens early in the course of graft rejection [12][13][14][15][16]. The hereby-reported results might therefore be associated with appropriate immune suppression medication doses and overall good tolerance of grafted tissue.…”
Section: Resultsmentioning
confidence: 87%